2021
DOI: 10.3390/polym13060932
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hydrogel Scaffolds Based on Alginate, Gelatin, 2-Hydroxyethyl Methacrylate, and Hydroxyapatite

Abstract: Hydrogel scaffolding biomaterials are one of the most attractive polymeric biomaterials for regenerative engineering and can be engineered into tissue mimetic scaffolds to support cell growth due to their similarity to the native extracellular matrix. The novel, versatile hydrogel scaffolds based on alginate, gelatin, 2-hydroxyethyl methacrylate, and inorganic agent hydroxyapatite were prepared by modified cryogelation. The chemical composition, morphology, porosity, mechanical properties, effects on cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 81 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…ALGH-HAP scaffolds have been prepared in conjunction with several other polymers, such as gelatin (Gel) [ 71 , 72 , 73 ], chitosan (Chit) [ 72 , 74 , 75 ], fibrin [ 76 ], polyvinyl alcohol [ 77 ], polylactic acid [ 78 , 79 ], ethyl cellulose and poly(Ɛ-caprolactone) [ 80 ] and other polymers [ 81 , 82 ]. Figure 4 shows composite ALGH-HAP scaffolds, containing Gel.…”
Section: Algh-hap Scaffoldsmentioning
confidence: 99%
“…ALGH-HAP scaffolds have been prepared in conjunction with several other polymers, such as gelatin (Gel) [ 71 , 72 , 73 ], chitosan (Chit) [ 72 , 74 , 75 ], fibrin [ 76 ], polyvinyl alcohol [ 77 ], polylactic acid [ 78 , 79 ], ethyl cellulose and poly(Ɛ-caprolactone) [ 80 ] and other polymers [ 81 , 82 ]. Figure 4 shows composite ALGH-HAP scaffolds, containing Gel.…”
Section: Algh-hap Scaffoldsmentioning
confidence: 99%
“…Without further modification, alginate dialdehyde has been used to synthesize hydrogels with gelatin in the presence of borax [55], while Emami et al studied the physical properties of these hydrogels by controlling the concentration of alginate solution and oxidation condition [90]. With the addition of 2-hydroxyethyl methacrylate (HEMA) and the presence of hydroxyapatite (HAp), a porous alginate hydrogel is synthesized [94]. The hydrogel is synthesized with the cyrogelation method, where the additional compounds enhance the mechanical properties and biocompatibility.…”
Section: Oxidation and Reductionmentioning
confidence: 99%
“…Alg hydrogels alone or in combination with other polymers have been investigated extensively as hydrogel-based inks for bioprinting due to their low toxicity [10,13,14], structural resemblance of extracellular matrices [10,13,14] and biocompatibility [10,13]. Additionally, the sol-gel transition of alginate solution induced by crosslinking with divalent ions of calcium makes them a potential candidate for bioprinting and tissue regeneration [14,[16][17][18]. Studies have reported that Alg with a high M content is more immunogenic than Alg with a high G content [10,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers have found that Alg is limited in providing sufficient structural stability and mechanical properties to generate robust structures after printing [10,19,20]. To overcome these challenges, Alg composite ink solutions were developed by mixing Alg with other substances, such as gelatin [21], chitosan [22], collagen [23], polycaprolactone [24], polyvinyl alcohol [25], polylactic acid [26] and inorganic compounds such as hydroxyapatite [16] and tetraethyl orthosilicate [27]. Furthermore, the mechanical and structural properties of Alg ink can be enhanced by adding nanomaterials such as graphene [28] and carbon nanotubes [29].…”
Section: Introductionmentioning
confidence: 99%